ELECTRONIC INFORMATION AND EDUCATIONAL ENVIRONMENT OF THE UNIVERSITY AS A MEANS OF ORGANIZING INDEPENDENT WORK OF STUDENTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
In the context of the modernization of Russian higher education, training should be built on a differentiated basis, have a problematic and developing character. The main purpose of higher education is to prepare a graduate who is not just knowledgeable but who knows how to apply his knowledge. In this regard, there is a need for continuous self-education and self-development, in the development of selection skills useful for students of professional development and improvement of information. At the same time the efforts of the teacher should be aimed at creating an environment focused on independence, interactivity, productivity of students' activities, an environment that provides an opportunity to form an individual educational experience of a student moving along their own educational path. To organize effective independent work of students it is advisable to create an integrated system for organizing this work based on the information and educational environment of the university. The article presents the experience of organizing independent work of students of the Arzamas branch of Nizhny NovgorodStateUniversity through the electronic information and educational environment of the university. The article describes the developed electronic courses in the disciplines of the psychological-pedagogical cycle, shows the importance of such areas of independent work of students when using the electronic educational environment of the university as the search for the necessary information; preparation for practical, laboratory, seminar classes; preparation for the survey, colloquium; test preparation; preparation for tests and other types of written test works; preparation for various competitions, contests and more.